CONSUMERS’ PERCEPTION OF SUSTAINABLE PACKAGING IN THE FOOD INDUSTRY: AN ONLINE EXPERIMENT - Anquez, Elsa; Raab, Katharina; Cechella, Felipe Schneider; Wagner, Ralf (Revista Direitos Culturais, 2022)
Consumers evaluate products and make purchasing decisions based on packaging and its sustainable aspects. This research investigated how different packages and their quality, eco-friendliness, expensiveness, and convenience affected consumers’ intentions to purchase. Our sample comprised 299 French consumers of muesli cereals. We conducted an online choice experiment to analyze and measure consumers’ perception of sustainable packaging, comparing three distinct experimental groups. Findings revealed that quality and environmental friendliness impact purchase intentions. Price sensitivity and environmental behavior showed to have moderation effects in the proposed research model. The reusable container is perceived as more expensive and less convenient when compared to other packaging types. We contribute to the existing literature in the food industry by providing additional insights into consumers’ recognition processes in identifying sustainable packaging.